Real-time PCR for differential quantification of CVI988 vaccine virus and virulent strains of Marek’s disease virus - Baigent, Susan J. (J Virol Methods, 2016)
CVI988/Rispens vaccine, the ‘gold standard’ vaccine against Marek’s disease in poultry, is not easily distinguishable from virulent strains of Marek’s disease herpesvirus (MDV). Accurate differential measurement of CVI988 and virulent MDV is commercially important to confirm successful vaccination, to diagnose Marek’s disease, and to investigate causes of vaccine failure. A real-time quantitative PCR assay to distinguish CVI988 and virulent MDV based on a consistent single nucleotide polymorphism in the pp38 gene, was developed, optimised and validated using common primers to amplify both viruses, but differential detection of PCR products using two short probes specific for either CVI988 or virulent MDV. Both probes showed perfect specificity for three commercial preparations of CVI988 and 12 virulent MDV strains. Validation against BAC-sequence-specific and U(S)2-sequence-specific q-PCR, on spleen samples from experimental chickens co-infected with BAC-cloned pCVI988 and wild-type virulent MDV, demonstrated that CVI988 and virulent MDV could be quantified very accurately. The assay was then used to follow kinetics of replication of commercial CVI988 and virulent MDV in feather tips and blood of vaccinated and challenged experimental chickens. The assay is a great improvement in enabling accurate differential quantification of CVI988 and virulent MDV over a biologically relevant range of virus levels.